Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.5539/ies.v8n5p150
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Computer-Mediated Communication in Project Work

Abstract: In line with the new trend of using computer-mediated communication (CMC) as an innovative technique in teaching and learning at higher institutions, Facebook as a channel of CMC was employed in carrying out a project work in an Academic Communication Course. For this project, students worked in groups to discuss their work and share information using both CMC and face-to-face interactions. An open ended questions survey was administered to these undergraduate students who were assigned to investigate a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…2020) that shows PjBL-STEM learning improves students' higher-order thinking skills. Furthermore, these findings are consistent with Musa et al, (2012) research, which indicated that the use of integrated PjBL applications improves 21st-century abilities influenced by application, one of which is the ability to think creatively.…”
Section: Resultssupporting
confidence: 88%
“…2020) that shows PjBL-STEM learning improves students' higher-order thinking skills. Furthermore, these findings are consistent with Musa et al, (2012) research, which indicated that the use of integrated PjBL applications improves 21st-century abilities influenced by application, one of which is the ability to think creatively.…”
Section: Resultssupporting
confidence: 88%
“…In a similar vein, several authors reported that the use of Facebook as an LMS had the potential to engage students even in out‐of‐class discussion with instructors and to increase student motivation, peer learning and feedback (Albayrak & Yildirim, ; Bariş & Tosun, ; Geyer, ; Karal et al, ; Miron & Ravid, ; Musa et al, ; O'Bannon, Beard, & Britt, ; O'Bannon, Britt, & Beard, ; Omar, Embi, & Yunus, ; Öztürk, ; Rachtam, Kaewkitipong, & Firpo, ; Rubrico & Hashim, ; Shih, ; Shraim, ; Souleles, ; Staines & Lauchs, ; Stankov, Glavinić, & Krpan, ; Varol, ; Vincent & Weber, ; Wang, Leng, & Lee, ).…”
Section: Formal Use Of Facebook In Formal Settings Of Learningmentioning
confidence: 98%
“…Similarly, learners are thrilled to learn English in social media platforms such as Facebook, WhatsApp, Instagram and YouTube (Ghounane, 2020). Learners from all over the world can interact and discuss a range of topics on these social networking sites (Musa, Mohamed, Mufti, Latiff, & Amin, 2015). The use of mobile-mediated communication allows learners to study not only the standard form of the language, but also its varieties.…”
Section: Intervention Of Social Media and Video Conferencing Tools To Help Esl Learners Coping With The Challenges During Covid-19 Pandemmentioning
confidence: 99%